Polyurethane biodegradation by Serratia sp. HY-72 isolated from the intestine of the Asian mantis Hierodula patellifera - Kim, Jong-Hoon; Choi, Seung Hoon; Park, Min Gu; Park, Dong Hwan; Son, Kwang-Hee; Park, Ho-Yong (Frontiers in Microbiology, 2022)
Polyurethane (PU), currently replacing existing synthetic materials worldwide, is a synthetic polymer derived from polyols, isocyanates, and a chain extender added by condensation reactions. PU wastes which are difficult to recycle, are commonly discarded in landfills and flow into ecosystems, thereby causing serious environmental problems. In recent years, insect-associated microbes have become a promising, eco-friendly strategy as an alternative to plastic recycling. This study aimed to evaluate the potential of Serratia sp. HY-72 strain isolated from the intestine of the Asian mantis (Hierodula patellifera) for PU degradation. The 65 kDa family I.3 lipase which degrades PU was identified and characterized, with a specific activity of 2,883 U mg-1. The bacterial filtrates and the recombinant lipase degraded Impranil (a colloidal polyester-PU dispersion, 100 g l-1) by 85.24% and 78.35% after 72 h incubation, respectively. Fourier transform infrared spectroscopy analysis revealed changes in Impranil functional groups, with decreased C=O functional group and aliphatic chain signals, and increased N-H bending with C-N stretching and C-O stretching. The current study also revealed that the HY-72 strain biodegraded the commercial PU foams (polyester- and polyether- PU) with 23.95% and 10.95% weight loss after 2 weeks, respectively with changes in surface morphology and structure such as cracks, roughness, and surface roughening. Altogether, this is one of the few studies reporting biodegradation of PU by the insect-associated microbe. These findings suggest that the insect-associated microbe could be a promising resource for biodegradation and recycling of plastic waste.